2015
DOI: 10.1038/srep15998
|View full text |Cite
|
Sign up to set email alerts
|

What Has Caused Desertification in China?

Abstract: Desertification is the result of complex interactions among various factors, including climate change and human activities. However, previous research generally focused on either meteorological factors associated with climate change or human factors associated with human activities, and lacked quantitative assessments of their interaction combined with long-term monitoring. Thus, the roles of climate change and human factors in desertification remain uncertain. To understand the factors that determine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 27 publications
0
85
0
2
Order By: Relevance
“…Changes in pasture areas also occurred as result of transformation both from and into barren land (797.53 and 571.5 km 2 , respectively). These changes were caused by climate change, which in turn, led to the extension of pasture into high altitudes and desertification (Feng et al, ). In order to compare the net transformation according to different land‐use types, Table shows the predominating forms of changes.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in pasture areas also occurred as result of transformation both from and into barren land (797.53 and 571.5 km 2 , respectively). These changes were caused by climate change, which in turn, led to the extension of pasture into high altitudes and desertification (Feng et al, ). In order to compare the net transformation according to different land‐use types, Table shows the predominating forms of changes.…”
Section: Resultsmentioning
confidence: 99%
“…Feng et al used a pooled regression model to consider the relative roles of climate change and human activities on desertified areas and vegetation coverage. The results showed that socioeconomic factors were the dominant factors affecting desertification [24]. Lü et al [25] quantified the changing trends in vegetation using the FVC estimated by remote sensing and analyzed the influential factors.…”
Section: Introductionmentioning
confidence: 99%
“…In the YLC region, the forest increased mainly due to the conversion from the pasture (63.65 km 2 ), which is primarily attributed to the afforestation programs and ecological environment restoration programs in Qilian mountain launched in early 2000s [43]. Pasture area increased results from the conversion from barren land (226.03 km 2 ), which is due to the global warming that led to pasture extending to higher altitude area [33]. The other two conversion types in YLC are pasture to farm land (13.3 km 2 ) and glacier to barren land (28.37 km 2 ), which occupies about 12% of total land use conversion area.…”
Section: Calibration and Validation Of Swat Modelmentioning
confidence: 99%
“…The total annual runoff is 16.05 × 10 8 m 3 with significant interannual variability [31]. Conditions within the Heihe River have attracted great attention in China due to increasing pressures in the nation, particularly in water resources and the degradation of natural environmental sectors [32,33]. [28].…”
Section: Introductionmentioning
confidence: 99%